STRATEGI KOMUNIKASI HUMAS POLDA RIAU DALAM MEMPUBLIKASIKAN INFORMASI MELALUI WEBSITE WWW.TRIBRATANEWSRIAU.COM - Laras Pradina Gunawan; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The existence of news that is not factual, not accurate and objective, not concrete and well-balanced that are quoted from incompetent source from outsiders or Indonesia Police Department (Polri) internal side can cause a bias towards case substances or the problem being published as the news.That is why, public relations of Polda Riau should provide a trusted and competent mass media. www.tribratanewsriau.com is one of the new media used by Polda Riau public relations to publish their work for the citizen in the form of news portal containing police department's activities, especially in Riau. www.tribratanewsriau.com website exists to give trusted and objective information. The purpose of this study is to know how is the communication sytrategy of Riau Police Department public relations from communicator strategy, message strategy and media strategy in publishing informations through www.tribratanews.com website. A good strategy will make the website an effective media to deliver informations. This study used qualitative methods. Data collecting techniques used are interview, observation, and documentation. The informants of this study consist of four people in which all of them are also the main informant. Data analysis technique used is descriptive analysis bu Huberman and Miles. Data validation are done by triangulation and extension of participation. This study shows that communicator strategy in publishing information which all Polda Riau personnel has the ability to do this because they already trained in public relations before. Aside from the human resources aspect, communicator also get the facility to support their work performance. Communication messages delivered are the informative and educative messages. Information published must be consistent by making monthly report of website recaps. The website is managed with settings that can be easily accessed by the user. Keyword: communication sytrategy, Riau Police Department, publishing information